CORRELATION OF EOSINOPHIL CATIONIC PROTEIN WITH SEVERITY OF ASTHMA - Badar, Ahmed; Saeed, Waseem; Hussain, M Mazhar; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: Activated eosinophils play an important role in the pathogenesis of bronchial asthma. Upon activation eosinophils release their granular proteins. Eosinophil Cationic Protein (ECP) is a highly basic protein of ribonuclease-A family that is released from matrix of eosinophil granules. In the recent past a number of studies have shown increased levels of ECP in serum and induced sputum of asthmatics. We carried out this study to find out correlation of serum ECP with severity of asthma. Methods: This study was carried out on 44 asthmatics and 44 matched controls at Department of Physiology, Army Medical College, Rawalpindi from June 2002 to December 2003. Lung function tests were done using spirometer (Vitalograph-Compact) and severity of asthma was graded into four classes, mild intermittent, mild persistent, moderate persistent and severe persistent. Serum was used to assess ECP by ELISA. Statistical correlation between ECP and severity of asthma as well as lung function tests was calculated. Results: The asthmatics as compared with the controls had significantly more serum ECP. Serum ECP increased significantly with increase in severity of asthma (from mild intermittent to severe persistent). Serum ECP was negatively correlated with FEV1 and FEV1/FVC(r=-.823 and r=-.772, p<.001 respectively). There was a significant positive correlation between serum ECP and severity of asthma (r=0.947 p<0.001) Conclusions: We conclude from this study that serum ECP can be used as a useful laboratory investigation for severity of asthma. Keywords: Asthma, Eosinophil, Eosinophil Cationic Protein, ECP